DEVELOPMENT OF A BOOKLET AS A NUTRITION EDUCATIONAL MEDIA IN HYPERTENSION PATIENTS - Isnaini, Futwi; Larasati, Meirina Dwi; Ambarwati, Ria; Jaelani, Mohammad; Prihatin, Setyo (JURNAL KESMAS DAN GIZI (JKG), 2023)
Background: Leaflet media is limited to only writing, so it is necessary to develop booklet media that present short messages accompanied by pictures so that they are easily accepted and understood as an alternative media that supports efforts to increase knowledge and understanding regarding the management of a hypertension diet. Objective: To develop and determine the feasibility of a booklet as a nutritional education medium for people with hypertension based on assessments from media experts and material experts. Method: Research and Development with the ADDIE model includes 5 stages, namely needs analysis, planning, development, testing and evaluation. Booklet evaluation was carried out by material experts and media experts using the CVI (Content Validity Index) which was then tested on 10 respondents with hypertension using a questionnaire. The media eligibility criteria are based on scores with very appropriate categories (81% -100%), appropriate (61% -80%), sufficiently feasible (41% -60%), less feasible (21% -40%), and not feasible (0-20%). Descriptive data analysis. Results: The CVI assessment according to material experts and booklet media experts obtained a score (> 0.8) worthy of being used as a media for nutrition education and the results of the respondent's trial obtained a score (87.25%) in the very feasible category. Conclusion: The media booklet on the management of hypertension is appropriate to be used as a media for nutrition education.